2021
DOI: 10.3389/fneur.2021.642877
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clot Shape on Successful M1 Endovascular Reperfusion

Abstract: Objectives: The susceptibility-vessel-sign (SVS) allows thrombus visualization, length estimation and composition, and it may impact reperfusion during mechanical thrombectomy (MT). SVS can also describe thrombus shape in the occluded artery: in the straight M1-segment (S-shaped), or in an angulated/traversing a bifurcation segment (A-shaped). We determined whether SVS clot shape influenced reperfusion and outcomes after MT for proximal middle-cerebral-artery (M1) occlusions.Methods: Between May 2015 and March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Specifically, thrombi at MCA bifurcations can be localized in the distal M1 involving a single M2 branch. 6) Guenego et al demonstrated that thrombi in the M2 extension had a low rate of successful reperfusion compared with a straight distal M1 thrombus. 6) In cases of an M1 with a single M2 thrombus, partial thrombus complement by stent retrieval from the non-buried M2 branch has a risk of fragmentation, leading to incomplete revascularization and distal embolization during the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, thrombi at MCA bifurcations can be localized in the distal M1 involving a single M2 branch. 6) Guenego et al demonstrated that thrombi in the M2 extension had a low rate of successful reperfusion compared with a straight distal M1 thrombus. 6) In cases of an M1 with a single M2 thrombus, partial thrombus complement by stent retrieval from the non-buried M2 branch has a risk of fragmentation, leading to incomplete revascularization and distal embolization during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“… 6) Guenego et al demonstrated that thrombi in the M2 extension had a low rate of successful reperfusion compared with a straight distal M1 thrombus. 6) In cases of an M1 with a single M2 thrombus, partial thrombus complement by stent retrieval from the non-buried M2 branch has a risk of fragmentation, leading to incomplete revascularization and distal embolization during the procedure. 11) Multiple thrombectomy procedures can also increase the risk of procedural complications due to endothelial injury and naturally prolong the ischemic interval.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations